To find the number of zeros of the function \( f(x) = x(x - 1)(2x + 4)^2 \), we can analyze each factor of the function.
-
The first factor is \( x \). This factor has a zero at \( x = 0 \).
-
The second factor is \( (x - 1) \). This factor has a zero at \( x = 1 \).
-
The third factor is \( (2x + 4)^2 \). The linear factor \( 2x + 4 = 0 \) gives a zero at: \[ 2x + 4 = 0 \implies 2x = -4 \implies x = -2 \] Since this factor is squared, the zero at \( x = -2 \) has a multiplicity of 2.
Now, let's count the total number of zeros including their multiplicities:
- From \( x \): 1 zero (at \( x = 0 \))
- From \( (x - 1) \): 1 zero (at \( x = 1 \))
- From \( (2x + 4)^2 \): 2 zeros (at \( x = -2 \), counted twice)
Adding these together, we get: \[ 1 + 1 + 2 = 4 \]
Thus, the function \( f(x) = x(x - 1)(2x + 4)^2 \) has 4 zeros, including repeated zeros.
The correct answer is 4.